A systematic review of economic evaluations of tyrosine kinase inhibitors for non-small cell lung cancer (NSCLC). (24th July 2022) - Byun, Joo-Young; Park, Sun-Kyeong; Ng, Boon Peng; Liu, Yi-Shao; Kim, Chae-Rin; Park, Chanhyun
ABSTRACT: Introduction: Although tyrosine kinase inhibitors (TKIs) have improved the efficacy of treatment for non-small cell lung cancer (NSCLC), the accessibility of TKIs is limited due to high costs. Despite the critical role of the cost-effectiveness of TKIs on decision-making, no systematic reviews have compared the cost-effectiveness of comparable TKIs. Therefore, we systemically reviewed the economic evaluation studies on various TKIs for NSCLC. Areas covered: We searched PubMed and the Cochran Library to identify the published economic evaluation studies of TKIs in NSCLC patients that were published by January 2022. All of the included studies ( n = 38) evaluated the cost-effectiveness of epidermal growth factor receptor (EGFR)-TKIs ( n = 29) or anaplastic lymphocyte kinase (ALK)-TKIs ( n = 9). The cost-effectiveness results were reported as the incremental cost-effectiveness ratio per quality-adjusted life-year, except for three studies. Expert opinion: We found that the economic evaluation studies of the first and second generation of EGFR-TKIs and ALK-TKIs varied by the country and study settings, such as comparator and input parameters. In 12 studies, osimertinib (EGFR-TKI) was not cost-effective compared to other first/second EGFR-TKIs, regardless of the study settings. More evidence can be provided about cost-effectiveness of the third-generation TKIs in future research.